Pedagogical Fundamentals Of Development Of Social Activity On The Basis Of Formation Of Standard Competencies In Students - Dilorom Khoshimova; N. Khamziddinov (Procedia of Social Sciences and Humanities, 2022)
In this article, the content of the formation of social activity on the basis of the formation of basecompetences in students, the ability to overcome conflicts and problems that have arisen as a component ofsocial activity, the contribution of students to the development of a worthy place in the future microsium, theanalysis of important components of social activity, which are not always